2012
DOI: 10.1001/archoto.2011.1474
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Expression in Nasal Polyps of Aspirin-Intolerant Patients

Abstract: Nasal polyps from aspirin-tolerant and aspirin-intolerant patients are characterized by strong proliferation and high levels of VEGF and neuropilin expression. Nasal polyps from aspirin-intolerant patients show distinctly increased VEGF levels. The relevance of these findings for future therapeutic approaches is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…For example, we detected a possible interaction of basal EpC VEGF with receptors on endothelial cells ( Figure 4B ). This is consistent with several reports identifying increased VEGF in nasal polyp tissue ( 48 , 49 ), and in the lower airway VEGFA from EpCs has been implicated in signaling to endothelial cells to promote angiogenesis in obstructive lung disease ( 50 , 51 ). We also detected a possible interaction of endothelial cell HB-EGF (heparin-binding EGF-like growth factor) with basal EpC receptors ( Figure 4B ), which may be involved in regulating EpC tissue remodeling in CRSwNP.…”
Section: Discussionsupporting
confidence: 93%
“…For example, we detected a possible interaction of basal EpC VEGF with receptors on endothelial cells ( Figure 4B ). This is consistent with several reports identifying increased VEGF in nasal polyp tissue ( 48 , 49 ), and in the lower airway VEGFA from EpCs has been implicated in signaling to endothelial cells to promote angiogenesis in obstructive lung disease ( 50 , 51 ). We also detected a possible interaction of endothelial cell HB-EGF (heparin-binding EGF-like growth factor) with basal EpC receptors ( Figure 4B ), which may be involved in regulating EpC tissue remodeling in CRSwNP.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study [29] demonstrated high levels of VEGF in nasal polyps enhanced proliferation by activating VEGF receptors and downstream pathways, subsequently promoting polyps formation. VEGF is a family of homodimeric proteins that consisted by six members, including VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E and placenta growth factor [30].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is widely recognized as a major proangiogenic factor involved in the process of neovascularization and vascular leakage through VEGF receptor-mediated pathways in tissue remodeling [ 28 ]. Previous study [ 29 ] demonstrated high levels of VEGF in nasal polyps enhanced proliferation by activating VEGF receptors and downstream pathways, subsequently promoting polyps formation. VEGF is a family of homodimeric proteins that consisted by six members, including VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E and placenta growth factor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased level of VEGF is also found in the nasal lavage of chronic rhinosinusitis patients with nasal polyposis ( 181 ). The increased PGD 2 levels in nasal polyps of patients with chronic rhinosinusitis has been identified as a dominant factor in inducing the production of VEGF via the DP receptors, and an increased level of VEGF has been documented in nasal polyps of N-ERD patients ( 24 , 182 , 183 ). In N-ERD, overexpression of PGD 2 may explain the increase in VEGF, and suppression of VEGF production could be a potential mechanism, by which nasal polyp recurrence is reduced in N-ERD.…”
Section: Potential Mechanism Of Aspirin Actionmentioning
confidence: 99%